The Efficacy of the Persian Version of the Mindfulness-Based Stress Management App (Aramgar) for College’s Mindfulness Skills and Perceived Stress - Borjalilu, Somaieh (Universitas Muhammadiyah Yogyakarta, 2023)
Functional mobile applications are one of the brand-new approaches to psychological interventions in different areas, including stress. The study aims to analyze a mobile application for Persian users on perceived stress and improve mindful skills. This study is a one-group pretest-posttest design with a quasi-experimental research design. Three instruments were used in this study, including the Five Factor Mindfulness Questionnaire (FFMQ), the Perceived Stress Scale (PSS-10), and the Mobile App Rating Scale (MARS). Eighty-five students participated in an 8-week mindfulness mobile app (Aramgar) for at least 10 minutes per day intervention. They responded to validated outcome measures of stress and mindfulness at baseline after the 8-week continued access period. Aramgar is designed based on mindfulness-based stress reduction. Paired t-tests showed significant differences in general perceived stress (P = 0.03) and total score of mindfulness (P = 0.002) before and after Aramgar. The analysis of Aramgar’s quality regarding engagement, functionality, aesthetics, and information quality showed that specialists assessed the quality appropriately. Using functional mobile apps provides simplicity for mental health services. Therefore, to strengthen and develop the mentioned services, it is recommended that the necessary information technology infrastructures be provided and limitations for designing and running mental health mobile apps be removed.